Emergence and Spread of Plasmid-Borne tet(B)::ISCR2 in Minocycline-Resistant Acinetobacter baumannii Isolates - Vilacoba, Elisabet (2013)
Resistance to minocycline has emerged in multidrug-resistant Acinetobacter baumannii isolates from Buenos Aires Hospitals. Few reports about the description and dispersion of tet genes were published in this species. We observed the presence of tet(B) in all minocycline resistant isolates. This gene was found associated to the ISCR2 mobile element, which could in part explain its dispersion.